PCR-DGGE Based Biodiveristy, Changeability and Genetic Similarity Analysis of Bacterial Community in Sequencing Batch Reactors Dealing with Reject Water - Aleksandra ZIEMBIŃSKA-BUCZYŃSKA; Grzegorz CEMA; Marta SZPINDOR; Anna MERESTA; Lesław PŁONKA (Engineering Transactions, 2014)
Reject water, produced during stabilization and dewatering of activated sludge, contains a high load of biogenic compounds which are returned to bioreactors, so there is a necessity for its treatment within biological systems. The efficacy of such performance depends mainly on the activated sludge composition responsible for the biochemical processes. For biocenosis diversity and changeability, PCR-DGGE is the most commonly used tool. In this article we monitor the activated sludge bacterial communities of two sequencing batch reactors (SBRs) dealing with reject water but varying in their operational parameters. A physico-chemical analysis of the SBRs performance was also done. We used two different PCR primers sets to present a total overview of the changeability in complex microbial biocenosis during wastewater treatment. For biodiversity monitoring 16S rRNA gene fragments amplified with 338f-GC/518r primers appeared to be more suitable than the fragments amplified with 968f-GC/1401r – the index was higher though the changes were proportional for both cases. The results were confirmed with genetic similarity analysis presented as dendrograms.